2016
DOI: 10.1002/jctb.5025
|View full text |Cite
|
Sign up to set email alerts
|

Alumina coating with TiO2and its effect on catalytic photodegradation of phenol andp-cresol

Abstract: BACKGROUND This study is focused on the peptization of Boehmite and titanium alkoxide (modified sol–gel method) to obtain Al2O3–TiO2 mixed oxides taking advantage of the physicochemical properties of TiO2 and Al2O3. TiO2 is an important semiconductor and the most active photocatalyst. Al2O3 is an insulator with high surface area and thermal, chemical and mechanical resistance. It is possible to produce high surface area materials, where TiO2 is dispersed on the alumina surface for photodegradation of pollutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…However, it has important scale-up limitations such as the high and pH-dependent recombination rate, a low absorption of solar light, and the low to moderate surface area of most commercial TiO 2 -based photocatalysts, which limits their application to low effluent volumes and low pollutants concentration [3,4]. It has been extensively reported than most of these limitations can be overcome by using various co-supports such as alumina [5], silica [6,7], and activated carbon [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has important scale-up limitations such as the high and pH-dependent recombination rate, a low absorption of solar light, and the low to moderate surface area of most commercial TiO 2 -based photocatalysts, which limits their application to low effluent volumes and low pollutants concentration [3,4]. It has been extensively reported than most of these limitations can be overcome by using various co-supports such as alumina [5], silica [6,7], and activated carbon [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the absorption of substrate molecules will be promoted by the alumina porous support and by the forced permeation of reagents through the catalytic membrane pores . The efficiency of the supported-TiO 2 photocatalyst could also be enhanced, since alumina is able to trap the photogenerated (e – ) and (h + ) charges, delaying their recombination. ,, Moreover, it has been proved that, by extending the interfacial contact surface between the TiO 2 semiconductor and Al 2 O 3 support, important surface defects are created at the alumina–titania interface, which act as active sites for photodegradation …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, semiconductor photocatalytic processes have been shown to have great potential as a low-cost, environmentally friendly, and sustainable technology for wastewater treatment and environmental remediation. Compared with other materials, titanium dioxide (TiO 2 )-based photocatalysts are the most attractive due to the multiple advantages that they display: (i) high efficiency, (ii) structural stability, (iii) nontoxicity, and (iv) ready availability. , Their ability to remove refractory organic pollutants and microorganisms in water by photooxidative processes has been widely demonstrated by using both artificial and natural lights. , The main research efforts have been addressed to modify the TiO 2 structural and electronic properties, with the aim of improving the photocatalyst efficiency and extending their photoresponse into the visible region. The main strategies adopted to reach these aims comprise impurity-doping, dye anchoring, design of TiO 2 nanohybrids, or defect-engineered (including Ti 3+ self-doped) nanophases. The use of charge transfer catalysts (CTCs), such as Al 2 O 3 , to prepare TiO 2 -based photocatalysts is an alternative way of improving the photocatalytic activities. These composite binary oxides frequently exhibit unexpected properties derived from a synergistic interaction between the two components. Indeed, Al 2 O 3 hosting materials are proved to trap the photogenerated charges, delaying their recombination, and to enhance the adsorption ability of the photocatalyst for target molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They supported the idea that the coating blocks the transfer of both photo-generated holes and electrons by the reduction of photocatalytic oxidation and photocatalytic reduction. Gomez et al [42] created coatings with a mixture of 𝛼-alumina and TiO 2 . Their study concluded that the presence of Al 2 O 3 decreases the electron-hole recombination as it acts as a charge transfer catalyst.…”
Section: Mass Transport and Reaction Modelmentioning
confidence: 99%